2014
DOI: 10.1002/jms.3401
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the optimization space for atmospheric pressure photoionization (APPI) in comparison with APCI

Abstract: The usefulness of atmospheric pressure photoionization (APPI) is difficult to evaluate for unknowns due to the fragmented literature. Specifically, the variation of dopants with a wide set of compounds or the use of APPI in the negative mode have rarely been explored. Thirty compounds were selected that were not suitable for ESI with a wide variety of functional groups and investigated with atmospheric pressure chemical ionization (APCI) and APPI in the positive and negative ion modes. The influence of the mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
1
12
1
Order By: Relevance
“…Based on the data presented in Figure 4, it was concluded that the sensitivity of PSCI was improved with the usage of solvents in the order of hexane < toluene < chlorobenzene. These data are consistent with a previous study, which suggested chlorobenzene as a sensitive dopant for molecular ion generation during atmospheric pressure photoionization (APPI) 44 . Previous studies showed that chemical reactions such as charge transfer and/or proton transfer between solvent and analyte are important for APPI mechanism 45–47 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the data presented in Figure 4, it was concluded that the sensitivity of PSCI was improved with the usage of solvents in the order of hexane < toluene < chlorobenzene. These data are consistent with a previous study, which suggested chlorobenzene as a sensitive dopant for molecular ion generation during atmospheric pressure photoionization (APPI) 44 . Previous studies showed that chemical reactions such as charge transfer and/or proton transfer between solvent and analyte are important for APPI mechanism 45–47 .…”
Section: Resultssupporting
confidence: 93%
“…These data are consistent with a previous study, which suggested chlorobenzene as a sensitive dopant for molecular ion generation during atmospheric pressure photoionization (APPI). 44 Previous studies showed that chemical reactions such as charge transfer and/or proton transfer between solvent and analyte are important for APPI mechanism. [45][46][47] Therefore, there is a common element shared by PSCI, atmospheric pressure chemical ionization, and APPI mechanisms, and that can explain the improved ionization efficiency with chlorobenzene for both APPI and PSCI.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, influence of mobile phases on ionization in an APCI source was studied by Fredenhagen and Kühnöl and it was concluded that for APCI+ mobile phases containing MeOH were advantageous compared with MeCN. For some compounds with MeCN signal‐to‐noise ratios were higher; however, this was due to an extensive in‐source fragmentation while utilizing MeOH as organic mobile phase.…”
Section: Introductionmentioning
confidence: 99%
“…The ionization mechanisms in the DA‐NI‐APPI, as well as the role of commonly used eluents and buffers in LC and the effect of operational parameters of MS on the observed ions in the mass spectra, have been studied thoroughly. A summary of ionization pathways in the NI‐APPI mode, which were adopted from the literature, is presented in Table .…”
Section: Resultsmentioning
confidence: 99%